2006
DOI: 10.1111/j.1365-2354.2005.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care treatment patterns and associated costs of healthcare resource use for specific advanced cancer patients in the UK

Abstract: The purpose of this paper is to identify the treatment patterns and corresponding costs of healthcare resource use associated with palliative care for different types of advanced cancer patients, from the time they started strong opioid treatment until death. This was a modelling study performed from the perspective of the UK's National Health Service (NHS). A data set was created comprising 547 patients in the DIN-Link database who had a Read code for malignant neoplasms with a specific tumour-type diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 11 publications
2
53
0
Order By: Relevance
“…Cost of radiotherapy was based on a study by Ploquin and Dunscombe [43] and confirmed by local expert radiotherapy clinical opinion. The cost of best supportive care was obtained from a study conducted by Guest et al [44].…”
Section: Valuation Of Resourcesmentioning
confidence: 99%
“…Cost of radiotherapy was based on a study by Ploquin and Dunscombe [43] and confirmed by local expert radiotherapy clinical opinion. The cost of best supportive care was obtained from a study conducted by Guest et al [44].…”
Section: Valuation Of Resourcesmentioning
confidence: 99%
“…The palliative cost associated with ovarian cancer was estimated by Guest et al 112 to be £4789 (at 2000-1 prices) for an average time period of 399 days. This cost predominantly consisted of hospitalisation costs (71% of costs), updating the estimate of palliative care for patients with ovarian cancer from Guest et al 112 to current prices using the Hospital & Community Health Services index results in a cost of £6963, equating to £531 per month. This cost is applied monthly to all PRR patients following entry into the PD health state, and all platinum-sensitive patients following 6 months of residence in the PD health state.…”
Section: Stable Disease Health-state Costsmentioning
confidence: 99%
“…Resource use estimates were based on Study 19 [19], previous appraisals [28], clinical guidelines [14], literature [29][30][31] and assumptions. Unit costs were derived from NHS Reference Costs 2013-14 [32], the Personal Social Services Research Unit (PSSRU) [33], the NHS Commercial Medicines Unit (CMU) [34] and the BNF [12].…”
Section: Cost-effectiveness Evidence Submitted By the Companymentioning
confidence: 99%